Irrigação contínua e intermitente em arroz irrigado: uso de água, eficiência agronômica e dissipação de imazethapyr, imazapic e fipronil - Mezzomo, Rafael Friguetto (2009)
Every anthropogenic activity causes environmental impact in some extent. Rice paddy fields area are pointed out as an activity with high potential of pollution due to the large amount of water used to maintain the flooding and the intensive use of pesticides and nutrients that can be transported to the environment. Though, there are other irrigation management practices that can reduce the environmental impact caused by the rice farming. Based on that, the objective of this study was to investigate the effect of the continuous and intermittent flooding on the amount of water applied and the amount of water transported to the environment, on water use efficiency, on weed control, on agronomic parameters of the rice plants and on dissipation of imazethapyr, imazapic and fipronil. The intermittent flooding resulted in crop yield similar to continuous irrigation. In addition, it reduced in 32% the amount of water applied, resulting in a better water use efficiency (1.68 kg m-3) than the continuous flooding (1.14 kg m-3). Water saving is promoted by the higher amount of rainfall stored in the intermittent flooding. The intermittent flooding reduces 40% of the run-off and less environmental contamination, resulting, on the average of the three pesticides a reduction higher than 90% on the mass of pesticide transported to the environment in comparison to the total applied on the rice Field.